STRATEGIC AWARENESS AS A CATALYST FOR ORGANIZATIONAL CHANGE THROUGH THE MEDIATING ROLE OF ADMINISTRATIVE CREATIVITY: AN APPLIED STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES IN THE UNION FOOD INDUSTRIES COMPANY IN BABYLON GOVERNORATE - Ali Abd Al Razaq Alaboody (Journal Park Publishing, 2024)
The purpose of the current research is to reveal the role of strategic awareness in its dimensions (awareness of the external environment, awareness of the internal environment, awareness of the current situation, awareness of the current future) as a catalyst for organizational change in its dimensions (organizational structure, culture, human resources, advanced technology) through the mediating role of administrative creativity in its dimensions (originality, fluency, flexibility, sensitivity to problems) among a sample of employees in the Union Food Industries Company in Babylon Governorate. As it was distributed (140) questionnaire form to measure the level of availability of study variables, and retrieved (129) questionnaire by (11) damaged questionnaire, and (118) valid for analysis, and the research focused on modeling the structural equation in the interpretation and testing of hypotheses, and the research found a correlation and impact between strategic awareness and organizational change and administrative creativity, and this is what prompted a study to provide a set of recommendations came at the forefront of which the company surveyed to focus its interests on improving the capabilities of workers towards awareness of the external environment and Awareness of the internal environment, awareness of the current situation, awareness of the current future to stimulate their abilities to organizational change and compete with international companies through the mediating role of administrative creativity.
Keywords: strategic awareness, organizational change, administrative creativity